2009
DOI: 10.1002/app.30147
|View full text |Cite
|
Sign up to set email alerts
|

Nylon 6/Brazilian clay membranes prepared by phase inversion

Abstract: Microporous membranes were synthesized from a polymer nanocomposite material, intercalated montmorillonite clay/nylon 6, by an immersion-precipitation method in a water bath. This membrane was skinless and was composed of cellular pores and sheaflike crystallites, which were interwoven into a bicontinuous structure. In contrast, pure nylon 6, precipitated under the same conditions, yielded a skinned asymmetric membrane. The X-ray diffraction patterns showed that the nanocomposites and the membranes exhibited e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…However, in spite of the large number of works about polymer matrix/clay nanocomposites, only few works relate the use of organoclays of Brazilian origin. 2,[25][26][27][28][29][30][31][32][33][34] Most works use clays from American, Japanese and Chinese origin. 2,9,24 Therefore it is of great interest to study the organofilization of Brazilian clays and their resistance to temperature since to our knowledge, a systematic study on the thermal stability of Brazilian organoclays has never been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…However, in spite of the large number of works about polymer matrix/clay nanocomposites, only few works relate the use of organoclays of Brazilian origin. 2,[25][26][27][28][29][30][31][32][33][34] Most works use clays from American, Japanese and Chinese origin. 2,9,24 Therefore it is of great interest to study the organofilization of Brazilian clays and their resistance to temperature since to our knowledge, a systematic study on the thermal stability of Brazilian organoclays has never been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The Gaussian–Lorentzian function of Origin Pro® is exploited to plot the overlapping curves of the composites. 20–22 GFGMAPP gives rise the peaks at 285.14, 532.4, and 102.47 eV, which are responsible for C1s, O1s, and Si2p, respectively, while GFCFGMAPP engenders corresponding elemental peaks at 285.09, 532.1, and 102.52 eV. Further, GFCFFeGMAPP contains elements such as C1s (258.00 eV), O1s (532.18 eV), Si2p (102.24 eV), Fe (2p 1 at 728.26 eV, and 2p 3 at 710.08 eV), whereas GMAPP only consists of C1s (284.93 eV) and O1s (532.47 eV).…”
Section: Resultsmentioning
confidence: 99%
“…The Gaussian-Lorentzian function of Origin Pro® is exploited to plot the overlapping curves of the composites. [20][21][22] GFGMAPP gives rise the peaks at 285. 1 and S4 †).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The membranes were prepared by spreading this solution on a glass plate and rapidly immerged in a non-solvent bath (distilled water). After the precipitation time, the membranes were removed, washed with distilled water and dried at 60°C for 2 hours [12][13].…”
Section: Membranes Formationmentioning
confidence: 99%